Sharing the Growth Dividend : Analysis of Inequality in Asia - Jain-Chandra, Sonali; Kinda, Tidiane; Kochhar, Kalpana; Piao, Shi. (Washington, D.C. : International Monetary Fund, 2016)
This paper focusses on income inequality in Asia, its drivers and policies to combat it. It finds that income inequality has risen in most of Asia, in contrast to many regions. While in the past, rapid growth in Asia has come with equitable distribution of the gains, more recently fast-growing Asian economies have been unable to replicate the 'growth with equity' miracle. There is a growing consensus that high levels of inequality can hamper the pace and sustainability of growth. The paper argues that policies could have a substantial effect on reversing the trend of rising inequality. It is imperative to address inequality of opportunities, in particular to broaden access to education, health, and financial services. Also fiscal policy could combat rising inequality, including by expanding and broadening the coverage of social spending, improving tax progressivity, and boosting compliance. Further efforts to promote financial inclusion, while maintaining financial stability, can help.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet